A narrative analysis of young black South African women's stories about the recent divorce of their parents - Lotter, Jaclyn Oehley (Rhodes University, Faculty of Humanities, Department of Psychology, 2010)
The global rise in divorce since the 1960s has brought into question the idealised view of the nuclear family which has for centuries been awarded special status in western societies and has been regarded as the primary social institution. According to contemporary research parental divorce has become a reality for every one in six children in South Africa. Until recently, little consideration had been given to how divorce affects black South African families, as it was considered to be an occurrence which only took place in white, mainly middle-class, families. The proportion of black South African couples divorcing has been increasing over the past decade, and in 2008 was said to contribute to 35% of all divorce in South Africa. Most research to date on the children of divorce has focused on young white children and adolescents and is largely concerned with those who have found parental divorce particularly difficult, and are manifesting adjustment and other behavioural problems. The research which has been done on the effects of parental divorce on young adults focuses mainly on clinical studies with middle-class families based either in the United States or in the United Kingdom. This research, using an experience-centred, life-story narrative approach, explores the stories which young black South African adult women between the ages of 18 and 25 tell, to give account to the ways in which recent parental divorce has affected their lives, views on family life, and what it has meant to them. The use of an experience-centred, life-story narrative approach allows for a process of rupture, acceptance and re-storying to be accounted for, as the participant's narrative shifts from past, to present and the future. Five young black women from a South African university each participated in two narratively sequenced semi-structured interviews based on McAdams' personal narratives protocol, which includes six core themes, namely: Key Events, Significant People, Stresses and Problems, Personal Meanings and Life-Lessons, Future Script, and Life Theme. Crossley's narrative analysis was then used to identify emergent themes and images in each individual narrative, after which they were woven together into a coherent story linked to previous literature. This study found that divorce involves a highly complex transition and reconfiguration process perhaps not fully accounted for in the existing idea and images associated with it. Despite being young adult women who had moved away from home and were engaged in their own lives, it became apparent that parental divorce was still a difficult and complicated experience, but that it is possible to tell both pessimistic and optimistic stories of parental divorce and its consequences.
Keywords: Divorce -- South Africa; Divorce -- Psychological aspects -- South Africa; Children of divorced parents -- South Africa; Families -- South Africa; Divorce therapy -- South Africa; Adolescent psychotherapy -- South Africa; Youth, Black -- Counseling of -- South Africa; Psychology -- Biographical methods -- South Africa